A case of groove pancreatitis with duodenal stenosis successfully treated by endoscopic ultrasonography‐guided pancreaticogastrostomy. Issue 1 (30th November 2022) - Ikemura, Muneo; Tomishima, Ko; Ota, Hiroto; Kabemura, Daishi; Ushio, Mako; Fukuma, Taito; Takahashi, Sho; Suzuki, Akinori; Takasaki, Yusuke; Ito, Koichi; Ishii, Shigeto; Fujisawa, Toshio; et al.
Abstract: One of the reasons for groove pancreatitis is caused by the leakage of pancreatic juice into the space between the pancreatic head, descending duodenum, and common bile duct. Endoscopic drainage of Santorini's duct (SD) via the minor papilla is reportedly efficacious but can be difficult due to duodenal stenosis. We report Santorini's duct drainage using endoscopic ultrasonography‐guided pancreaticogastrostomy (EUS‐PGS) for a case of groove pancreatitis with gastric outlet obstruction. Gastric outlet obstruction was improved after 7 months of EUS‐PGS with internal drainage through the Santorini's duct/minor papilla. EUS‐PGS may be effective for treating groove pancreatitis with duodenal stenosis. This is the first report of groove pancreatitis with duodenal stenosis, the symptoms of which were improved by EUS‐PGS.